Theoretical analysis of the definition of «Creative Pedagogy» - Т. А. Ivashchenko; Е. S. Dvoynikovaon.ru (Вестник Майкопского государственного технологического университета)
In modern society knowledge of Creative Pedagogy ensures high potential of educational activities and achievement of a high level of education quality. The education system is faced with the task of qualitatively preparing a modern graduate for further education and work. Solving this problem requires the search and implementation of new teaching methods, which are a meaningful component of Creative Pedagogy. Scientific works do not fully present a comprehensive analysis of Creative Pedagogy. They primarily reveal only some aspects related to the creativity of a teacher and the principles of organizing a creative environment. The weak theoretical development of the issue under consideration allowed us to formulate the following research problem: what are the essential characteristics of Creative Pedagogy? The purpose of the article is to substantiate theoretical approaches to the definition of “Creative Pedagogy”. Solving the stated goal required the use of theoretical research methods (analysis of scientific literature, synthesis of existing knowledge on the problem under study, generalization). The empirical basis of the study is represented by analytical materials and information resources on the Internet.The results of the research include 1) the concept of “Creative Pedagogy” is considered as an innovative direction of the new education paradigm; 2) the potential of Creative Pedagogy in educational activities has been revealed; 3) the pedagogical conditions for the creative orientation of pedagogical activity have been determined; 4) the basic principles of creating a creative educational environment have been outlined.Key findings: The study extends pedagogical theory toward understanding the content of Creative Pedagogy; the presented basic principles can be used by teachers when organizing a creative educational environment, and the proposed creative teaching methods can be used to stimulate the cognitive activity of students.